2021
DOI: 10.1098/rsbl.2021.0260
|View full text |Cite
|
Sign up to set email alerts
|

Family-specific chemical profiles provide potential kin recognition cues in the sexually cannibalistic spider Argiope bruennichi

Abstract: Kin recognition, the ability to detect relatives, is important for cooperation, altruism and also inbreeding avoidance. A large body of research on kin recognition mechanisms exists for vertebrates and insects, while little is known for other arthropod taxa. In spiders, nepotism has been reported in social and solitary species. However, there are very few examples of kin discrimination in a mating context, one coming from the orb-weaver Argiope bruennichi . Owing to effective mating plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In this study, we identified for the first time wax esters with a bishomomethyl-branched acid head group that constitute the major portion of lipids on the cuticle of both sexes and web silk of females of A. bruennichi. These cuticular compounds likely play a role in kin recognition, because family differences were observed within the wax esters, while cuticular hydrocarbons showed lower variation (Weiss and Schneider 2021). We developed an analytical procedure that can reliably be used to analyze and characterize these esters, based on previous work (Chinta et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified for the first time wax esters with a bishomomethyl-branched acid head group that constitute the major portion of lipids on the cuticle of both sexes and web silk of females of A. bruennichi. These cuticular compounds likely play a role in kin recognition, because family differences were observed within the wax esters, while cuticular hydrocarbons showed lower variation (Weiss and Schneider 2021). We developed an analytical procedure that can reliably be used to analyze and characterize these esters, based on previous work (Chinta et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they survive copulation more often (Welke and Schneider 2010), allowing them to leave and search for another female. Recently some of us showed that kin-recognition might be mediated by cuticular compounds occurring in family-specific bouquets and suggested an important role of unusual long-chain esters in kin recognition (Weiss and Schneider 2021). We present here the identification and synthesis of the dominant group of compounds of these bouquets, long chain esters of 2,4-dimethylbranched acids with mostly unbranched fatty alcohols, and clarify their distribution.…”
Section: Introductionmentioning
confidence: 89%
“…In Hippodamia variegata Goeze (Xie et al ., 2022) and H. axyridis (Rondoni et al ., 2021), antennal transcriptomes have reported the presence of odorant receptors and their chemosensory role in prey recognition and searching behaviour. Studies involving the role of family-specific chemical profiles in kin recognition have also been reported (Wong et al , 2014; Weiss and Schneider, 2021). Thus, the first instars cannibalising the eggs first encountered either sibling or non-sibling eggs might be attributed to the recognition of similar egg surface chemicals that lowers the risk of consuming toxic food and increases the chances of survival by overcoming the initial period of vulnerability, however, it does not confirm the presence of kin recognition ability in any of the life stages except the third instars which cannibalised higher percentage of non-sibling eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of above-ground plant biomass provoked by chronic grazing (Tälle et al 2016; Pett and Bailey 2019; Ferreira et al 2020; da Silva Bomfim et al 2021) directly affects the primary hunting strategy of orb-weavers, the ability to build webs using the tridimensional vegetal structure (Nogueira and Pinto-da-Rocha 2016). Without physical structures to build their web, species are unable to find prey (Torma et al 2019; Helden et al 2020; Fischer et al 2021) and mates (Cory and Schneider 2018; Weiss and Schneider 2021), as well as avoid predation (Blackledge and Wenzel 1999; da Silva Bomfim et al 2021; Narimanov et al 2021). Consequently, the simplification of habitat structure induced by grazing can culminate in the decline of local populations, resulting in the exclusion of orb-weaver species from grasslands (Oyarzabal and Guimarães 2021).…”
Section: Introductionmentioning
confidence: 99%